2018
DOI: 10.1007/s00402-018-3006-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and microbiological effects of local vancomycin in anterior cruciate ligament (ACL) reconstruction: a porcine tendon model

Abstract: This study showed no signs of biomechanical impairment of porcine flexor tendons after the use of vancomycin wraps with concentration ranging from 1 to 10 mg/ml for 10 or 20 min at a time zero testing. Contamination with S. epidermidis was cleansed in 100% of tendons when using at least 5 mg/ml of vancomycin for 20 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…However, Domnick et al could demonstrate that for biomechanical investigations, fresh-frozen porcine flexor tendons represent an appropriate substitute for human semitendinosus tendons [20]. Both porcine flexor tendons and the mechanical setup in this study have been used in other investigations on the strength of suture-tendon constructs [12,[20][21][22][23]. Freezing the samples for storage might have influenced the material properties, but the tensile force gets lower because of freezing [20].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, Domnick et al could demonstrate that for biomechanical investigations, fresh-frozen porcine flexor tendons represent an appropriate substitute for human semitendinosus tendons [20]. Both porcine flexor tendons and the mechanical setup in this study have been used in other investigations on the strength of suture-tendon constructs [12,[20][21][22][23]. Freezing the samples for storage might have influenced the material properties, but the tensile force gets lower because of freezing [20].…”
Section: Discussionmentioning
confidence: 92%
“…The samples were thawed to room temperature for 12 h before the testing and cut to a length of 24 cm. Fresh-frozen porcine flexor tendons were used based on availability and comparable biomechanical properties compared to human tendons [20] and they had been established for similar testing setups in previous studies [21][22][23].…”
Section: Samplesmentioning
confidence: 99%
“…Some in vitro studies have shown significant efficacy of vancomycin pre-soaking to eradicate bacteria in cases of septic arthritis post anterior cruciate ligament reconstruction 14,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In their animal study on staphylococcus epidermidis infected tendons, Schuttler et al 14 demonstrated that pre-soaking for 20 minutes with high concentration vancomycin solution (5mg/ml) reduced bacterial growth after 7 days of culture from 85.7% to 0%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation